Consuming Atmospheres Designing, Experiencing, and Researching Atmospheres in Consumption Spaces (Taylor & Francis, 2024)
consuming atmospheres, marketing, marketing research, consumer experience, consumer culture
English
Keywords: Behavioural economics; Business and Management; Market research; Sales and marketing; consuming atmospheres, marketing, marketing research, consumer experience, consumer culture